Magneto-transport studies on La2/3Ba1/3(Mn1–x Alx)O3 for low field sensing applications - Abdullah, Huda; Shaari, Abdul Halim; Lim, Kean Pah; Azman, Nur Jannah (W. S. Maney & Son, 2009)
The magnetic and transport properties of La2/3Ba1/3(Mn1−x Al x )O3 (x=0·0, 0·1, 0·2, 0·3 and 0·4) compounds, prepared by the solid state reaction, have been investigated. Samples show a metal–insulator transition excluding the sample x=0·0. With increased Al doping, the metal–insulator transition temperature T p is shifted to lower temperatures. Grain size reduction leads to a larger resistivity and a decrease in T p. Upon analysing the data using several theoretical models, it was found that the metallic (ferromagnetic) part of the resistivity ρ (below T P) fits well with the equation ρ=ρ 0+ρ 2 T2, where ρ 0 is due to the importance of grain/domain boundary effects, and a second term ρ 2 T2 might be attributed to the electron–electron scattering. The microstructure results indicate that the porosity of the samples increased when the concentration increased. The magnetoresistance (MR) is defined as %MR=100×[ρ(H,T)–ρ(0,T)]/[ρ(0,T)], where ρ(H,T) and ρ(0,T) are the resistivities at temperature T, with an applied magnetic field H and zero applied magnetic field respectively. All samples show low-field magnetoresistance and high-field magnetoresistance regions. The highest percentage of LFMR at a temperature of 100 K is ∼210% MR/Tesla, measured for the sample x=0·2. For x=0·3, the sample reveals the highest colossal magnetoresistance value among other doped compounds with 27·27% at 100 K.